Energy-saving high-strength fence-type composite anode plate for nonferrous metal electrowinning and preparation method thereof

By using glass fiber surface lead metallized alloy layer and active silver nanoparticles on the anode plate to coat aluminum-titanium-boron composite particles, the low mechanical strength and titanium-based coating cost of lead-based alloy anode in the prior art are solved. High problem achieves efficient and long-life anode plate performance.

CN115807245BActive Publication Date: 2025-02-07KUNMING HENDERA SCI & TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211647945.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-21
Publication Date
2025-02-07
Estimated Expiration
2042-12-21

AI Technical Summary

Technical Problem

In the prior art, the lead-based alloy anode has problems such as high oxygen evolution overpotential, low mechanical strength, lead dissolution and contamination of metal products. Although the titanium-based coating can improve the quality of electrocalcined zinc, it is easy to passivate due to the titanium and The price is expensive, resulting in high costs, limiting the large-scale use of the anode.

Method used

Aluminum conductive beam is coated with aging-resistant and corrosion-resistant lead metallized alloy layer on the surface of glass fiber to prevent the conducting beam from crystallization and improve heat dissipation. A coolant circulation channel is set inside the conductive beam to pass through oxidation-resistant water to circulate and cool. . At the same time, active silver nanoparticles are introduced on the anode working surface to coat aluminum-titanium-boron composite particles with good conductivity and strong hardness, thereby improving electrocatalytic activity and service life.

Benefits of technology

It achieves high electrode strength, low tank voltage, long service life, less anode mud generated by the anode, and improves the quality of the cathode product, and the current density can be increased by 1 times during electrolysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115807245B_ABST
    Figure CN115807245B_ABST
Patent Text Reader

Abstract

The present invention relates to an energy-saving high-strength fence-type composite anode plate for nonferrous metal electrowinning and a preparation method thereof, and belongs to the technical field of nonferrous metallurgy. The composite anode plate of the present invention comprises an aluminum conductive beam, a copper-aluminum composite conductive head is fixedly arranged at the end of the aluminum conductive beam, a fence-type aluminum-based composite anode plate bracket is fixedly arranged at the bottom end of the aluminum conductive beam, and a plurality of horizontal conductive reinforcing ribs are fixedly arranged along the longitudinal direction on the fence-type aluminum-based composite anode plate bracket, and both sides of the fence-type aluminum-based composite anode plate bracket are covered with insulating sheaths, and the two ends of the conductive reinforcing ribs are arranged in the insulating sheaths; the fence-type aluminum-based composite anode plate bracket is composed of a plurality of parallel anode composite rods, and the anode composite rods include aluminum alloy rods, transition layers, lead-bismuth-antimony / rare earth-nano cobalt composite layers, and aluminum-titanium-boron particle surface-coated lead-silver composite coatings from the inside to the outside; wherein the transition layers include zinc layers, copper layers, and lead-tin-rare earth composite layers from the inside to the outside.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an energy-saving and high-strength fence-type composite anode plate for nonferrous metal electrodeposition and a preparation method thereof, belonging to the technical field of nonferrous metallurgy. Background Art

[0002] At present, the insoluble anode materials used for the extraction of non-ferrous and rare metals are mainly lead-based alloys and titanium-based coated anodes. In the process of non-ferrous metal electrodeposition, the performance of the anode material directly affects the indicators such as ion discharge potential, overpotential change, current efficiency, power consumption, anode life and cathode product quality. In the hydrometallurgical industry of zinc, copper, nickel, manganese and cobalt in China and even the world, lead alloys have been used as anode materials for more than 100 years. However, the key technical problems of lead alloy anodes such as high oxygen evolution overpotential, low mechanical strength, lead dissolution and pollution of metal products have not been fundamentally solved. Although titanium-based coatings can solve the problems of lead-based alloy anodes and improve the quality of electrolytic zinc deposition. However, titanium-based PbO2 anodes without intermediate layers are difficult to conduct electricity due to the easy passivation of titanium. In addition, the price of titanium is expensive and the production cost is high. Although the use of titanium-based anodes with intermediate layers can improve the firmness, conductivity and corrosion resistance of the anode to a certain extent, it further increases the cost, which limits the large-scale use of anodes.

[0003] Composite anodes are prepared by utilizing the light weight and excellent electrical conductivity of aluminum and the excellent electrochemical properties of lead alloys. Compared with the light weight of lead alloys, they have attracted widespread attention. Anodes are made by dissolving lightweight metal aluminum as the inner core and lead alloy as the outer layer through melting or electroplating. There are some difficult problems to solve. First, the fluidity of the lead alloy liquid and the possible local holes in large-sized anode plates cannot be solved. Second, some grain boundary gaps will appear in the coating. The oxygen generated during electrolysis will pass through the grain boundary gaps of the coating to oxidize the aluminum matrix, forming an aluminum oxide film with poor conductivity, which deteriorates the anode performance.

[0004] The fence-type anode plate used for hydrometallurgical metal extraction can increase the current density of the anode, improve the flow performance of the electrolyte, improve the effect and quality of electrolytic non-ferrous metal collection, and avoid the defect of the cathode plate touching the anode plate when it is lifted. The use of cheap aluminum rods as the substrate significantly reduces the material cost, but it still has problems such as high cell voltage, easy crystallization of the conductive beam surface and short circuit, the insulation sheath affects the distribution of power lines, reduces the output of cathode products, and has a short life. Summary of the invention

[0005] In view of the problems existing in the anode plates in the above-mentioned hydrometallurgy, the present invention provides an energy-saving high-strength fence-type composite anode plate for non-ferrous metal electrowinning and a preparation method thereof. The anode plate has high electrode strength, low cell voltage during electrolysis, long service life, less anode mud generated by the anode, and high quality cathode products. The present invention introduces an aging-resistant and corrosion-resistant glass fiber surface metallized lead alloy layer to coat the beam body, thereby preventing the conductive beam body from crystallizing and improving the heat dissipation. A coolant circulation channel is arranged in the conductive beam body and antioxidant water is introduced for circulation cooling to avoid the heating problem of the beam. Active silver nanoparticles are introduced into the anode working surface to coat aluminum-titanium-boron composite particles with good conductivity and strong hardness, thereby improving the electrocatalytic activity and service life of the anode. Compared with traditional lead-silver multi-element alloys, without changing the electrolytic cell structure, electrolyte composition and operating specifications, the anode prepared by the present invention has a 1-fold longer service life, less manganese dioxide particles coated on the electrode surface, a cell voltage reduced by more than 10%, a current efficiency increased by more than 3%, a cathode product of high quality, and a current density that can be increased by 1-fold during electrolysis.

[0006] An energy-saving and high-strength fence-type composite anode plate for non-ferrous metal electrowinning, comprising an aluminum conductive beam 1, a copper-aluminum composite conductive head 2 is fixedly arranged at the end of the aluminum conductive beam 1, a fence-type aluminum-based composite anode plate bracket 3 is fixedly arranged at the bottom of the aluminum conductive beam 1, a plurality of horizontal conductive reinforcing ribs 6 are fixedly arranged along the longitudinal direction on the fence-type aluminum-based composite anode plate bracket 3, both sides of the fence-type aluminum-based composite anode plate bracket 3 are covered with insulating sheaths 4, and both ends of the conductive reinforcing ribs 6 are arranged in the insulating sheaths 4;

[0007] The fence-type aluminum-based composite anode plate bracket 3 is composed of a plurality of parallel anode composite rods 7, which include, from the inside to the outside, an aluminum alloy rod 71, a transition layer 72, a lead-bismuth-antimony / rare earth-nano cobalt composite layer 73, and a lead-silver composite coating 74 coated on the surface of aluminum-titanium-boron particles; wherein the transition layer 72 includes, from the inside to the outside, a zinc layer, a copper layer, and a lead-tin-rare earth composite layer.

[0008] The copper-aluminum composite conductive head 2 is composed of an inner copper rod 22 and an aluminum cladding layer 21 .

[0009] The aluminum conductive beam 1 includes aluminum or aluminum alloy, glass fiber cloth and lead-tin layer from inside to outside.

[0010] A coolant circulation channel parallel to the aluminum conductive beam 1 is provided in the aluminum conductive beam 1 , and the coolant circulation channel is filled with coolant.

[0011] The height of the aluminum conductive beam 1 is 10-60 mm, the thickness is 10-40 mm, the thickness of the glass fiber cloth is 0.2-2 mm, the thickness of the lead-tin layer is 0.1-2 mm, and the diameter of the coolant circulation channel is 0.5-10 mm.

[0012] The inner copper rod 22 in the copper-aluminum composite conductive head 2 is a heterogeneous structure with a thickness of 5 to 20 mm; the aluminum coating layer 21 includes a tin transition layer and an aluminum surface layer, the tin transition layer is 1 to 10 μm thick, and the aluminum surface layer is 5 to 30 mm thick.

[0013] The thickness of the zinc layer in the transition layer 72 is 0.5-2 μm, the thickness of the copper layer is 3-8 μm, and the thickness of the lead-tin-rare-earth composite layer is 4-20 μm; the mass percentage of tin in the lead-tin-rare-earth composite layer is 5-30%, the mass percentage of rare earth is 0.01-0.5%, and the balance is lead.

[0014] Taking the mass fraction of the lead-bismuth-antimony / rare earth-nano-cobalt composite layer 73 as 100%, bismuth accounts for 0.01-1%, antimony accounts for 0.5-5%, rare earth accounts for 0.01-0.1%, nano-cobalt accounts for 0.01-0.5%, and the balance is Pb.

[0015] In the lead-silver composite coating 74 coated on the surface of the aluminum-titanium-boron particles, the particle size of the aluminum-titanium-boron particles is 0.05-0.5 mm, and the thickness of the lead-silver composite coating is 0.1-0.6 mm; taking the mass fraction of the lead-silver composite coating 74 coated on the surface of the aluminum-titanium-boron particles as 100%, lead accounts for 5-12%, silver accounts for 0.5-3.0%, titanium in the aluminum-titanium-boron particles accounts for 1-5%, boron accounts for 0.1-1%, and the remainder is aluminum.

[0016] The conductive reinforcing rib 6 is a lead-tin-antimony alloy reinforcing rib, with the mass fraction of the lead-tin-antimony alloy being 100%, lead accounts for 88-98%, tin accounts for 1-6%, and antimony accounts for 1-6%.

[0017] Preferably, the conductive reinforcing rib 6 has a width of 10 to 100 mm and a thickness of 6 to 20 mm.

[0018] The method for preparing the energy-saving and high-strength fence-type composite anode plate for non-ferrous metal electrowinning comprises the following specific steps:

[0019] 1) The aluminum wire is sequentially subjected to alkaline washing, deionized water washing, ultrasonic cleaning, acid activation treatment, deionized water washing, zinc immersion treatment, deionized water washing, pyrophosphate copper plating treatment, deionized water washing, methanesulfonate lead-tin rare earth alloy plating treatment, deionized water washing, fluoroboric acid system lead-bismuth-antimony-rare earth nano-cobalt powder treatment, deionized water washing, extrusion and drawing composite rod treatment, pickling and oil removal, deionized water washing and drying, spraying of aluminum-titanium-boron composite particles coated with lead and silver on the surface, heat treatment, winding and cutting to a fixed length to obtain an anode composite rod;

[0020] Preferably, the alkaline washing solution contains 10-100 g / L NaOH and 5-20 g / L Na2CO3, the alkaline washing temperature is 50-70°C, and the alkaline washing soaking time is 20-100 s;

[0021] Preferably, the acid activation solution contains 20-50% nitric acid and 1-5% tartaric acid in mass percentage, and the acid activation treatment time is 5-30s;

[0022] Preferably, the zinc immersion solution contains 15-30 g / L zinc oxide, 80-120 g / L NaOH, 10-30 g / L potassium sodium tartrate, 0.5-2 g / L ferric chloride and 0.5-1.5 g / L nickel sulfate, and the zinc immersion treatment time is 30-60 s;

[0023] Preferably, the pyrophosphate copper plating solution contains 50-100 g / L copper pyrophosphate, 200-400 g / L potassium pyrophosphate, 5-20 g / L ammonium citrate and 1-5 g / L propylene glycol, the anode of the pyrophosphate copper plating is electrolytic copper, the electroplating temperature is 40-70°C, the cathode current density is 1-6 A / dm 2 , time is 3 to 30 minutes;

[0024] Preferably, the methanesulfonate lead-tin rare earth alloy plating solution contains 80-120 g / L lead methanesulfonate, 5-20 g / L stannous methanesulfonate, 60-120 g / L methanesulfonic acid, 2-10 g / L CeO2, 1-10 ml / L emulsifier and 0.05-1 g / L PVP; the anode of the methanesulfonate lead-tin rare earth alloy plating is a lead-tin alloy, and the cathode current density is 1-5 A / dm 2 , electroplating temperature is 20~50℃, time is 10~90min;

[0025] Preferably, the fluoroboric acid system lead bismuth antimony-rare earth nano cobalt powder solution contains 150-300 g / L lead acetate, 50-200 g / L fluoroboric acid, 2-12 g / L antimony potassium tartrate, 2-10 g / L CeO2, 1-6 g / L nano cobalt powder, 0.05-2 g / L gelatin and 0.05-1 g / L polyethylene glycol 6000. The anode of the fluoroboric acid system lead bismuth antimony-rare earth nano cobalt powder is a lead antimony alloy and the cathode current density is 3-10 A / dm 2 , the electroplating temperature is 20-60℃, and the time is 30-120min;

[0026] Preferably, the temperature of the extrusion-drawing composite rod treatment is 100-300°C, and the pulling speed is 1-10 m / min;

[0027] Preferably, the pickling solution contains 50-300 g / L sodium acetate, 10-200 g / L glucose and 1-20 g / L tartaric acid;

[0028] Preferably, the heat treatment temperature is 300-500° C. and the time is 3-5 min.

[0029] Preferably, the method for treating the aluminum-titanium-boron composite particles coated with lead-silver on the spray surface comprises the following specific steps:

[0030] S1. The aluminum titanium boron particles are degreased by sodium hydroxide solution, activated by HNO3 solution, roughened by HCl solution, sensitized by stannous chloride solution, and activated by silver nitrate solution or PdCl2 solution to obtain pretreated aluminum titanium boron particles;

[0031] Preferably, the concentration of sodium hydroxide solution is 5-10%, the concentration of HNO3 solution is 5-10%, the concentration of HCl solution is 5-10%, the concentration of stannous chloride solution is 10-30 g / L, the concentration of silver nitrate solution is 1-3 g / L, and the concentration of PdCl2 solution is 0.05-0.3 g / L;

[0032] S2. placing the pretreated aluminum-titanium-boron particles in a chemical lead-silver plating solution for chemical composite plating, washing with deionized water, and performing solid-liquid separation to obtain aluminum-titanium-boron composite particles coated with lead-silver;

[0033] Preferably, the chemical lead-silver plating solution contains 10-20 g / L PbCl2, 10-40 g / L nitrilotriacetic acid, 10-50 g / L sodium citrate, 3-10 ml / L TiCl3 (mass concentration is 20%) and 1-5 g / L nano silver powder, the pH value of the chemical lead-silver plating solution is 7.0-8.0, and the time of chemical composite plating is 30-120 min;

[0034] S3. Spraying the lead-silver coated aluminum-titanium-boron composite particles onto the surface of the extruded and drawn composite rod.

[0035] 2) The copper-aluminum composite conductive head is welded to one end of the aluminum conductive beam, and the anode composite rod is welded to the bottom end of the aluminum conductive beam to form a fence-type aluminum-based composite anode plate bracket. A plurality of conductive reinforcing ribs are horizontally die-cast on the fence-type aluminum-based composite anode plate bracket. Insulating sheaths are installed on both sides of the fence-type aluminum-based composite anode plate bracket. Insulators are installed on the fence-type aluminum-based composite anode plate bracket to obtain an energy-saving and high-strength fence-type composite anode plate for non-ferrous metal electrolysis.

[0036] The method for preparing the aluminum conductive beam comprises the following specific steps:

[0037] S1. Sensitizing and activating the glass fiber cloth, then immersing it in an alkaline chemical tin plating solution for tin plating for 5 to 30 minutes, and then placing it in an alkaline electroplating lead-tin solution for electroplating a lead-tin alloy for 0.5 to 8 hours to obtain a lead-tin alloy composite layer coated on the surface of the glass fiber cloth;

[0038] The sensitizing solution is stannous chloride solution, the sensitizing temperature is 20-40°C, and the sensitizing time is 2-20 minutes;

[0039] The activation solution is a silver nitrate solution, the activation temperature is 10-30°C, and the activation time is 2-10 minutes;

[0040] Preferably, the alkaline chemical tin plating solution contains 50-150 g / L sodium stannate and 10-30 g / L potassium hydroxide, the pH value of the alkaline chemical tin plating solution is 10-12, and the tin plating temperature is 50-70° C.;

[0041] Preferably, the alkaline lead-tin plating solution contains 10-30 g / L lead oxide, 20-40 g / L sodium stannate, 60-200 g / L potassium sodium tartrate and 10-40 g / L disodium ethylenediaminetetraacetic acid, the pH of the alkaline lead-tin plating solution is 11-13, the temperature of the lead-tin alloy electroplating is 30-50°C, and the current density is 0.5-2 A / dm 2 ;

[0042] S2. The aluminum or aluminum alloy beam is sandblasted and then activated with hydrochloric acid, and then placed in an alkaline chemical tinning solution for 5 to 30 minutes, and then a cooling liquid circulation channel parallel to the aluminum or aluminum alloy beam is opened in the aluminum or aluminum alloy beam to obtain a chemically tinned aluminum or aluminum alloy beam;

[0043] Preferably, the mass concentration of hydrochloric acid is 5-20%, and the hydrochloric acid activation treatment time is 0.5-10 min;

[0044] Preferably, the alkaline chemical tin plating solution contains 50-150 g / L sodium stannate and 10-30 g / L potassium hydroxide, the pH value of the alkaline chemical tin plating solution is 10-12, and the tin plating temperature is 50-70° C.;

[0045] S3. Covering the surface of the glass fiber cloth obtained in step S1 with a lead-tin alloy composite layer and coating the chemically tin-plated aluminum or aluminum alloy beam obtained in step S2 with rosin oil, and then subjecting the coating to heat treatment at a temperature of 100 to 200° C. to obtain an aluminum conductive beam.

[0046] The preparation method of the copper-aluminum composite conductive head comprises the following specific steps:

[0047] S1. The copper substrate is washed with sulfuric acid and deionized water and then immersed in an acidic chemical tin plating solution, tinned at a temperature of 40 to 80 ° C for 20 to 60 minutes, washed with deionized water and dried to obtain a chemically tinned copper substrate;

[0048] Preferably, the copper substrate is a T1 copper substrate;

[0049] Preferably, the acidic chemical tin plating solution contains 20-40 g / L of stannous chloride, 10-40 g / L of nitrilotriacetic acid, 40-80 g / L of thiourea, 20-40 ml / L of concentrated hydrochloric acid, 20-60 g / L of sodium citrate and 20-60 g / L of sodium hypophosphite, and the pH value of the acidic chemical tin plating solution is 0.5-2;

[0050] S2. placing the chemically tinned copper substrate in the mold cavity, extruding the aluminum alloy filling the cavity at a temperature of 600 to 700 ° C, cooling and crystallizing at a constant pressure to obtain a copper-aluminum composite conductive head;

[0051] Preferably, the extrusion pressure is 1-6 MPa, and the extrusion rate is 6-12 m / s.

[0052] The beneficial effects of the present invention are:

[0053] (1) The energy-saving high-strength fence-type composite anode plate for non-ferrous metal electrowinning of the present invention has good electrocatalytic activity, high strength and long service life. Compared with the traditional lead-silver multi-element alloy, the anode prepared by the present invention has a 1-fold longer service life without changing the electrolytic cell structure, electrolyte composition and operating specifications, less manganese dioxide particles are coated on the electrode surface, the cell voltage is reduced by more than 10%, the current efficiency is increased by more than 3%, the cathode product quality is high, and the current density during the electrolysis process can be increased by 1-fold;

[0054] (2) The present invention adopts the glass fiber surface metallization with strong aging resistance and corrosion resistance, so that the surface of the aluminum beam is well protected, and a large amount of aluminum sulfate crystal salt will not be generated due to the exposure of aluminum during the electrolysis process, and the heat dissipation of the beam body is well protected;

[0055] (3) The present invention sets a circulating coolant channel inside the aluminum beam, and introduces antioxidant water to circulate and cool the aluminum beam, thereby solving the heating problem of the beam body, reducing the interface resistance of the entire beam, and improving the conductivity of the beam body;

[0056] (4) The anode composite rod of the present invention can be produced by fully automated assembly line operation, which has a high degree of mechanization, can save labor costs, and improve efficiency. Its high degree of standardization makes the produced fence-type anode plate have good consistency, thereby improving the consistency of current during electrolysis and improving current efficiency;

[0057] (5) The present invention utilizes the high hardness of the lead-bismuth-antimony alloy and the good catalytic activity of rare earth and nano-cobalt powders to compositely electrodeposit a lead-bismuth-antimony / rare earth-nano-cobalt powder layer in a fluoroboric acid system, thereby increasing the deposition current density and obtaining a thicker lead alloy coating. The obtained fence-type anode plate has high strength and good electrocatalytic activity;

[0058] (6) The present invention uses lead-silver alloy to coat aluminum-titanium-boron particles to obtain composite particles, and utilizes the corrosion resistance and high conductivity of aluminum-titanium-boron and the corrosion resistance and catalytic activity of lead-silver, and based on the characteristic that the electrochemical reaction occurs at the liquid interface, the electrocatalytic activity of the anode is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 This is a schematic diagram of the structure of an energy-saving, high-strength fence-type composite anode plate for nonferrous metal electrowinning;

[0060] Figure 2 for Figure 1 AA cross-sectional diagram of ;

[0061] Figure 3 for Figure 1 BB cross-sectional diagram;

[0062] In the figure: 1-aluminum conductive beam, 11-aluminum substrate, 12-glass fiber cloth surface composite lead-tin layer, 2-copper-aluminum composite conductive head, 21-aluminum in the copper-aluminum composite conductive head, 22-copper in the copper-aluminum composite conductive head, 3-fence type aluminum-based composite anode plate bracket, 4-insulating sheath, 5-insulator, 6-conductive reinforcement rib, 7-anode composite rod, 71-aluminum alloy, 72-transition layer, 73-lead-bismuth-antimony / rare earth-nano-cobalt composite layer, 74-aluminum-titanium-boron particle surface coated with lead-silver composite coating. DETAILED DESCRIPTION

[0063] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.

[0064] like Figures 1 to 3 As shown, the energy-saving and high-strength fence-type composite anode plate for non-ferrous metal electrowinning of the present invention comprises an aluminum conductive beam 1, a copper-aluminum composite conductive head 2 is fixedly provided at the end of the aluminum conductive beam 1, a fence-type aluminum-based composite anode plate bracket 3 is fixedly provided at the bottom end of the aluminum conductive beam 1, and multiple layers of horizontal conductive reinforcing ribs 6 are fixedly provided along the longitudinal direction on the fence-type aluminum-based composite anode plate bracket 3, and both sides of the fence-type aluminum-based composite anode plate bracket 3 are covered with insulating sheaths 4, and both ends of the conductive reinforcing ribs 6 are arranged in the insulating sheaths 4;

[0065] The fence-type aluminum-based composite anode plate support 3 is composed of a plurality of parallel anode composite rods 7, which include, from the inside to the outside, an aluminum alloy rod 71, a transition layer 72, a lead-bismuth-antimony / rare earth-nano cobalt composite layer 73, and a lead-silver composite coating 74 coated on the surface of aluminum-titanium-boron particles; wherein the transition layer 72 includes, from the inside to the outside, a zinc layer, a copper layer, and a lead-tin-rare earth composite layer;

[0066] The thickness of the zinc layer in the transition layer 72 is 0.5-2 μm, the thickness of the copper layer is 3-8 μm, and the thickness of the lead-tin-rare-earth composite layer is 4-20 μm; the mass percentage of tin in the lead-tin-rare-earth composite layer is 5-30%, the mass percentage of rare earth is 0.01-0.5%, and the balance is lead; taking the mass fraction of the lead-bismuth-antimony / rare earth-nano-cobalt composite layer 73 as 100%, bismuth accounts for 0.01-1%, antimony accounts for 0.5-5%, and rare earth accounts for 0.01-0.1%. Nano-cobalt accounts for 0.01-0.5%, and the balance is Pb; in the lead-silver composite coating 74 coated on the surface of the aluminum-titanium-boron particles, the particle size of the aluminum-titanium-boron particles is 0.05-0.5 mm, and the thickness of the lead-silver composite coating is 0.1-0.6 mm; based on the mass fraction of the lead-silver composite coating 74 coated on the surface of the aluminum-titanium-boron particles as 100%, lead accounts for 5-12%, silver accounts for 0.5-3.0%, titanium in the aluminum-titanium-boron particles accounts for 1-5%, boron accounts for 0.1-1%, and the balance is aluminum;

[0067] The copper-aluminum composite conductive head 2 is composed of an inner copper rod 22 and an aluminum coating layer 21; the inner copper rod 22 in the copper-aluminum composite conductive head 2 is a heterogeneous structure with a thickness of 5 to 20 mm; the aluminum coating layer 21 includes a tin transition layer and an aluminum surface layer, the tin transition layer has a thickness of 1 to 10 μm, and the aluminum surface layer has a thickness of 5 to 30 mm;

[0068] The aluminum conductive beam 1 includes aluminum or aluminum alloy, glass fiber cloth and lead-tin layer from inside to outside;

[0069] A coolant circulation channel parallel to the aluminum conductive beam 1 is provided in the aluminum conductive beam 1, and the coolant circulation channel is filled with coolant; the height of the aluminum conductive beam 1 is 10-60 mm, the thickness is 10-40 mm, the thickness of the glass fiber cloth is 0.2-2 mm, the thickness of the lead-tin layer is 0.1-2 mm, and the diameter of the coolant circulation channel is 0.5-10 mm;

[0070] The conductive reinforcing rib 6 is a lead-tin-antimony alloy reinforcing rib, with the mass fraction of the lead-tin-antimony alloy being 100%, lead accounting for 88-98%, tin accounting for 1-6%, and antimony accounting for 1-6%; the conductive reinforcing rib 6 has a width of 10-100 mm and a thickness of 6-20 mm;

[0071] The preparation method of energy-saving high-strength fence type composite anode plate for non-ferrous metal electrowinning comprises the following specific steps:

[0072] 1) The aluminum wire is sequentially subjected to alkaline washing, deionized water washing, ultrasonic cleaning, acid activation treatment, deionized water washing, zinc immersion treatment, deionized water washing, pyrophosphate copper plating treatment, deionized water washing, methanesulfonate lead-tin rare earth alloy plating treatment, deionized water washing, fluoroboric acid system lead-bismuth-antimony-rare earth nano-cobalt powder treatment, deionized water washing, extrusion and drawing composite rod treatment, pickling and oil removal, deionized water washing and drying, spraying of aluminum-titanium-boron composite particles coated with lead and silver on the surface, heat treatment, winding and cutting to a fixed length to obtain an anode composite rod;

[0073] 2) The copper-aluminum composite conductive head is welded to one end of the aluminum conductive beam, and the anode composite rod is welded to the bottom end of the aluminum conductive beam to form a fence-type aluminum-based composite anode plate bracket. A plurality of conductive reinforcing ribs are horizontally die-cast on the fence-type aluminum-based composite anode plate bracket. Insulating sheaths are installed on both sides of the fence-type aluminum-based composite anode plate bracket. Insulators are installed on the fence-type aluminum-based composite anode plate bracket to obtain an energy-saving and high-strength fence-type composite anode plate for non-ferrous metal electrolysis.

[0074] The present invention introduces an aging-resistant and corrosion-resistant metallized lead alloy layer on the surface of glass fiber to coat the beam body, thereby preventing the conductive beam body from crystallizing and improving the heat dissipation. A coolant circulation channel is arranged in the conductive beam body and antioxidant water is introduced for circulation cooling to avoid the heating problem of the beam. Active silver nanoparticles are introduced to coat aluminum-titanium-boron composite particles with good conductivity and strong hardness on the working surface of the anode, thereby improving the electrocatalytic activity and service life of the anode. Compared with the traditional lead-silver multi-element alloy, the life of the anode prepared by the present invention is extended by 1 times, the number of manganese dioxide particles covering the electrode surface is less, the cell voltage is reduced by more than 10%, the current efficiency is increased by more than 3%, the cathode product quality is high, and the current density during the electrolysis process can be increased by 1 times without changing the electrolytic cell structure, electrolyte composition and operating specifications.

[0075] Example 1: This example is an energy-saving high-strength fence-type composite anode plate for non-ferrous metal electrowinning (see Figures 1 to 3 ); comprising an aluminum conductive beam 1, a copper-aluminum composite conductive head 2 is fixedly provided at the end of the aluminum conductive beam 1, a fence-type aluminum-based composite anode plate bracket 3 is fixedly provided at the bottom end of the aluminum conductive beam 1, and multiple layers of horizontal conductive reinforcing ribs 6 are fixedly provided along the longitudinal direction of the fence-type aluminum-based composite anode plate bracket 3, and both sides of the fence-type aluminum-based composite anode plate bracket 3 are covered with insulating sheaths 4, and both ends of the conductive reinforcing ribs 6 are arranged in the insulating sheaths 4; the insulating sheaths 4 are used to fix the edge of the fence-type composite anode plate bracket, the insulator is used to fix the inside of the fence-type composite anode plate bracket, and the conductive reinforcing ribs 6 are used to fix the anode composite rod of the fence-type composite anode plate bracket;

[0076] The fence-type aluminum-based composite anode plate support 3 is composed of a plurality of parallel anode composite rods 7, which include, from the inside to the outside, an aluminum alloy rod 71, a transition layer 72, a lead-bismuth-antimony / rare earth-nano cobalt composite layer 73, and a lead-silver composite coating 74 coated on the surface of aluminum-titanium-boron particles; wherein the transition layer 72 includes, from the inside to the outside, a zinc layer, a copper layer, and a lead-tin-rare earth composite layer;

[0077] The thickness of the zinc layer in the transition layer 72 is 1 μm, the thickness of the copper layer is 5 μm, and the thickness of the lead-tin-rare-earth composite layer is 15 μm; the mass percentage of tin in the lead-tin-rare-earth composite layer is 20%, the mass percentage of rare earth is 0.2%, and the balance is lead; taking the mass fraction of the lead-bismuth-antimony / rare earth-nano cobalt composite layer 73 as 100%, bismuth accounts for 0.5%, antimony accounts for 3%, rare earth accounts for 0.06%, nano cobalt accounts for 0.2%, and the balance is Pb; in the lead-silver composite coating 74 coated on the surface of the aluminum-titanium-boron particles, the particle size of the aluminum-titanium-boron particles is 0.2mm, and the thickness of the lead-silver composite coating is 0.25mm; taking the mass fraction of the lead-silver composite coating 74 coated on the surface of the aluminum-titanium-boron particles as 100%, lead accounts for 8%, silver accounts for 2.0% (silver is 20nm nano silver powder), titanium accounts for 3%, boron accounts for 0.5%, and the balance is aluminum;

[0078] The copper-aluminum composite conductive head 2 is prepared by a die-casting method and consists of an inner copper rod 22 and an aluminum coating layer 21; the inner copper rod 22 in the copper-aluminum composite conductive head 2 is a heterogeneous structure with a thickness of 10 mm; the aluminum coating layer 21 includes a tin transition layer and an aluminum surface layer, the tin transition layer is 2 μm thick, and the aluminum surface layer is 10 mm thick;

[0079] The aluminum conductive beam 1 includes 6061 aluminum alloy, glass fiber cloth and lead-tin layer from inside to outside in sequence; a coolant circulation channel parallel to the aluminum conductive beam 1 is opened in the aluminum conductive beam 1, and the coolant circulation channel is filled with anti-oxidation circulating water to cool the aluminum conductive beam; the height of the aluminum conductive beam 1 is 40 mm, the thickness is 20 mm, the thickness of the glass fiber cloth is 1 mm, the thickness of the lead-tin layer is 1.5 mm, and the diameter of the coolant circulation channel is 5 mm;

[0080] The conductive reinforcing rib 6 is a lead-tin-antimony alloy reinforcing rib, with the mass fraction of the lead-tin-antimony alloy being 100%, lead accounting for 95%, tin accounting for 3%, and antimony accounting for 2%; the conductive reinforcing rib 6 has a width of 60 mm and a thickness of 10 mm;

[0081] The preparation method of energy-saving high-strength fence type composite anode plate for non-ferrous metal electrowinning comprises the following specific steps:

[0082] 1) Preparation of aluminum conductive beam: The preparation method of the aluminum conductive beam includes the following specific steps:

[0083] S1. The glass fiber cloth was sensitized and activated at room temperature for 14 minutes, then immersed in an alkaline chemical tin plating solution for 15 minutes, and then placed in an alkaline electroplating lead-tin solution for electroplating lead-tin alloy for 4 hours to obtain a lead-tin alloy composite layer coated on the surface of the glass fiber cloth;

[0084] The sensitizing solution is 20g / LSnCI2+20ml / LHCl solution, and the sensitizing time is 7min;

[0085] The activation solution was 1 g / L PdCl2 solution, and the ultrasonic activation time was 7 min;

[0086] The alkaline chemical tin plating solution contains 100 g / L sodium stannate and 20 g / L potassium hydroxide, the pH value of the alkaline chemical tin plating solution is 11, the tin plating temperature is 60°C, and the mechanical stirring speed is 200 rpm;

[0087] The alkaline lead-tin plating solution contains 20g / L lead oxide, 30g / L sodium stannate, 120g / L potassium sodium tartrate and 30g / L disodium ethylenediaminetetraacetate. The pH of the alkaline lead-tin plating solution is 12. The temperature of the lead-tin alloy electroplating is 40°C and the current density is 1A / dm 2 ;

[0088] S2. The aluminum beam is sandblasted with 60 mesh SiC surface and then activated with hydrochloric acid, and then placed in an alkaline chemical tin plating solution for 15 minutes, and then a coolant circulation channel parallel to the aluminum or aluminum alloy beam is opened in the aluminum beam to obtain a chemically tinned aluminum beam; wherein the mass concentration of hydrochloric acid is 10%, and the hydrochloric acid activation treatment time is 5 minutes; the alkaline chemical tin plating solution contains 100g / L sodium stannate and 20g / L potassium hydroxide, the pH value of the alkaline chemical tin plating solution is 11, the tin plating temperature is 60°C, and the mechanical stirring speed is 200rpm;

[0089] S3. coating the surface of the glass fiber cloth obtained in step S1 with a lead-tin alloy composite layer and coating the chemically tin-plated aluminum or aluminum alloy beam obtained in step S2 with rosin oil, and then subjecting the beam to a heat treatment at a temperature of 150° C. to obtain an aluminum conductive beam;

[0090] 2) Preparation of copper-aluminum composite conductive head: The preparation method of the copper-aluminum composite conductive head has the following specific steps:

[0091] S1. The T1 copper substrate was pickled with 20% sulfuric acid and washed with deionized water, then immersed in an acidic chemical tin plating solution, tinned at a temperature of 60 ° C for 40 min, washed with deionized water and dried to obtain a chemically tinned copper substrate;

[0092] The acidic chemical tin plating solution contains 30 g / L stannous chloride, 30 g / L nitrilotriacetic acid, 60 g / L thiourea, 30 ml / L commercially available concentrated hydrochloric acid, 40 g / L sodium citrate and 40 g / L sodium hypophosphite, and the pH value of the acidic chemical tin plating solution is maintained at 1.0;

[0093] S2. The chemically tinned copper substrate is placed in the mold cavity, and the aluminum alloy is extruded into the cavity at a temperature of 670°C, and the copper-aluminum composite conductive head is obtained by cooling, crystallizing and solidifying at a constant pressure; wherein the extrusion pressure is 4MPa and the extrusion rate is 8m / s;

[0094] 3) The aluminum wire is sequentially subjected to alkaline washing, deionized water washing, ultrasonic cleaning, acid activation treatment, deionized water washing, zinc immersion treatment, deionized water washing, pyrophosphate copper plating treatment, deionized water washing, methanesulfonate lead-tin rare earth alloy plating treatment, deionized water washing, fluoroboric acid system lead-bismuth-antimony-rare earth nano-cobalt powder treatment, deionized water washing, extrusion and drawing composite rod treatment, pickling and oil removal, deionized water washing and drying, spraying of aluminum-titanium-boron composite particles coated with lead and silver on the surface, heat treatment, winding and cutting to a fixed length to obtain an anode composite rod;

[0095] The alkaline washing solution contains 60g / L NaOH and 10g / L Na2CO3, the alkaline washing temperature is 60℃, and the alkaline washing soaking time is 60s;

[0096] In terms of mass percentage, the acid activation solution contains 40% nitric acid and 3% tartaric acid, and the acid activation treatment time is 18s;

[0097] The zinc immersion solution contains 20 g / L zinc oxide, 100 g / L NaOH, 20 g / L potassium sodium tartrate, 1.0 g / L ferric chloride and 1.0 g / L nickel sulfate, and the zinc immersion treatment time is 40 s;

[0098] The pyrophosphate copper plating solution contains 60g / L copper pyrophosphate, 300g / L potassium pyrophosphate, 16g / L ammonium citrate and 3g / L propylene glycol. The anode of the pyrophosphate copper plating is copper, the electroplating temperature is 50°C, and the cathode current density is 3A / dm 2 , time is 20min;

[0099] The methanesulfonate lead-tin rare earth alloy plating solution contains 100g / L lead methanesulfonate, 12g / L stannous methanesulfonate, 100g / L methanesulfonic acid, 6g / L CeO2, 6ml / L emulsifier (emulsifier is OP-10) and 0.5g / L PVP; the anode of the methanesulfonate lead-tin rare earth alloy plating is Pb-3% Sn alloy, the cathode current density is 3A / dm 2 , electroplating temperature is 40℃, time is 60min;

[0100] The fluoroboric acid system lead bismuth antimony-rare earth nano cobalt powder plating solution contains 200g / L lead acetate, 100g / L fluoroboric acid, 8g / L antimony potassium tartrate, 6g / L CeO2, 3g / L nano cobalt powder, 1g / L gelatin, and 0.5g / L polyethylene glycol 6000; the anode of the fluoroboric acid system lead bismuth antimony-rare earth nano cobalt powder plating is Pb-1.5% Sb alloy, and the cathode current density is 6A / dm 2 , the electroplating temperature is 40℃ and the time is 90min;

[0101] The extrusion-drawn composite rod treatment was carried out in an extrusion coating machine, with a die temperature of 200 °C and a pulling speed of 6 m / min;

[0102] The pickling solution contains 180g / L sodium acetate, 100g / L glucose, and 10g / L tartaric acid;

[0103] The heat treatment is carried out in a hot air furnace at a temperature of 420°C for 5 minutes;

[0104] The method for treating aluminum-titanium-boron composite particles coated with lead-silver on the spray surface comprises the following specific steps:

[0105] S1. The aluminum titanium boron particles were degreased with a sodium hydroxide solution, activated with a HNO3 solution for 2 min, roughened with a HCl solution for 5 min, sensitized with a stannous chloride solution for 10 min, and activated with a silver nitrate solution for 5 min to obtain pretreated aluminum titanium boron particles;

[0106] The concentration of sodium hydroxide solution is 7%, the concentration of HNO3 solution is 7%, the concentration of HCl solution is 7%, the concentration of stannous chloride solution is 20g / LSnCI2+20ml / LHCl, and the concentration of silver nitrate solution is 3g / L;

[0107] S2. placing the pretreated aluminum-titanium-boron particles in a chemical lead-silver plating solution for chemical composite plating, washing with deionized water, and performing solid-liquid separation to obtain aluminum-titanium-boron composite particles coated with lead-silver;

[0108] The chemical lead-silver plating solution contains 15g / L PbCl2, 30g / L nitrilotriacetic acid, 30g / L sodium citrate, 6ml / L TiCl3 (mass concentration is 20%) and 3g / L nano silver powder. The pH value of the chemical lead-silver plating solution is adjusted to 8.0 by ammonia water, and the time of chemical composite plating is 90min.

[0109] S3. The lead-silver-coated aluminum-titanium-boron composite particles are sprayed on the surface of the extruded and drawn composite rod by a cold spray machine;

[0110] 4) welding the copper-aluminum composite conductive head and one end of the aluminum conductive beam, welding the anode composite rod to the bottom of the aluminum conductive beam to form a fence-type aluminum-based composite anode plate bracket, horizontally die-casting multiple layers of conductive reinforcing ribs on the fence-type aluminum-based composite anode plate bracket, installing insulating sheaths on both sides of the fence-type aluminum-based composite anode plate bracket, and installing insulators on the fence-type aluminum-based composite anode plate bracket to obtain an energy-saving and high-strength fence-type composite anode plate for non-ferrous metal electrowinning;

[0111] In this embodiment, the energy-saving high-strength fence-type composite anode plate for nonferrous metal electrowinning is electrolyzed in an acidic zinc electrolyte under the following electrolysis conditions: the zinc ion concentration of the electrolyte is 50 g / L, the sulfuric acid concentration is 160 g / L, and the Mn 2+ 12g / L, current density 800A / m 2 The electrolysis temperature is 40°C. The electrical efficiency of the gradient composite lead dioxide anode is 5.0% higher than that of the traditional lead-calcium (0.06%) and silver (0.3%) alloy anode plate, the cell voltage is reduced by 15%, the life is extended by 2.5 times, and the manganese dioxide particles covering the electrode surface are reduced by 80%.

[0112] Embodiment 2: The energy-saving high-strength fence type composite anode plate for non-ferrous metal electrowinning of this embodiment is basically the same as the energy-saving high-strength fence type composite anode plate for non-ferrous metal electrowinning of embodiment 1, except that: the thickness of the zinc layer in the transition layer 72 is 0.5 μm, the thickness of the copper layer is 3 μm, and the thickness of the lead-tin-rare earth composite layer is 4 μm; the mass percentage of tin in the lead-tin-rare earth composite layer is 5%, the mass percentage of rare earth is 0.01%, and the balance is lead; the mass fraction of the lead-bismuth-antimony / rare earth-nano cobalt composite layer 73 is 1 00%, bismuth accounts for 0.01%, antimony accounts for 0.5%, rare earth accounts for 0.01%, nano-cobalt accounts for 0.01%, and the balance is Pb; in the lead-silver composite coating 74 coated on the surface of the aluminum-titanium-boron particles, the particle size of the aluminum-titanium-boron particles is 0.05mm, and the thickness of the lead-silver composite coating is 0.1mm; taking the mass fraction of the lead-silver composite coating 74 coated on the surface of the aluminum-titanium-boron particles as 100%, lead accounts for 5%, silver accounts for 0.5% (silver is 10nm nano-silver powder), titanium accounts for 1%, boron accounts for 0.1%, and the balance is aluminum;

[0113] The copper-aluminum composite conductive head 2 is prepared by a die-casting method and consists of an inner copper rod 22 and an aluminum coating layer 21; the inner copper rod 22 in the copper-aluminum composite conductive head 2 is a heterogeneous structure with a thickness of 5 mm; the aluminum coating layer 21 includes a tin transition layer and an aluminum surface layer, the tin transition layer is 1 μm thick, and the aluminum surface layer is 5 mm thick;

[0114] The aluminum conductive beam 1 includes 6061 aluminum alloy, glass fiber cloth and lead-tin layer from inside to outside in sequence; a coolant circulation channel parallel to the aluminum conductive beam 1 is opened in the aluminum conductive beam 1, and the coolant circulation channel is filled with anti-oxidation circulating water to cool the aluminum conductive beam; the height of the aluminum conductive beam 1 is 20 mm, the thickness is 10 mm, the thickness of the glass fiber cloth is 0.2 mm, the thickness of the lead-tin layer is 0.1 mm, and the diameter of the coolant circulation channel is 0.5 mm;

[0115] The conductive reinforcing rib 6 is a lead-tin-antimony alloy reinforcing rib, with the mass fraction of the lead-tin-antimony alloy being 100%, lead accounting for 98%, tin accounting for 1%, and antimony accounting for 1%; the conductive reinforcing rib 6 has a width of 10 mm and a thickness of 6 mm;

[0116] The preparation method of energy-saving high-strength fence type composite anode plate for non-ferrous metal electrowinning comprises the following specific steps:

[0117] 1) Preparation of aluminum conductive beam: The preparation method of the aluminum conductive beam includes the following specific steps:

[0118] S1. The glass fiber cloth is sensitized and activated at room temperature, and then immersed in an alkaline chemical tin plating solution for tin plating for 5 minutes, and then placed in an alkaline electroplating lead-tin solution for electroplating lead-tin alloy for 0.5 hours to obtain a lead-tin alloy composite layer coated on the surface of the glass fiber cloth;

[0119] The sensitizing solution is 10g / LSnCI2+10ml / L HCl solution, and the sensitizing time is 2min;

[0120] The activation solution was 0.2 g / L PdCl2 solution, and the ultrasonic activation time was 2 min;

[0121] The alkaline chemical tin plating solution contains 50 g / L sodium stannate and 10 g / L potassium hydroxide, the pH value of the alkaline chemical tin plating solution is 10, the tin plating temperature is 50° C., and the mechanical stirring speed is 100 rpm;

[0122] The alkaline lead-tin plating solution contains 10g / L lead oxide, 20g / L sodium stannate, 60g / L potassium sodium tartrate and 10g / L disodium ethylenediaminetetraacetate. The pH of the alkaline lead-tin plating solution is 11. The temperature of the lead-tin alloy electroplating is 30°C and the current density is 0.5A / dm 2 ;

[0123] S2. The aluminum beam is sandblasted with 200 mesh SiC surface and then activated with hydrochloric acid, and then placed in an alkaline chemical tin plating solution for tin plating for 5 minutes, and then a coolant circulation channel parallel to the aluminum or aluminum alloy beam is opened in the aluminum beam to obtain a chemically tinned aluminum beam; wherein the mass concentration of hydrochloric acid is 10%, and the hydrochloric acid activation treatment time is 0.5 minutes; the alkaline chemical tin plating solution contains 50g / L sodium stannate and 10g / L potassium hydroxide, the pH value of the alkaline chemical tin plating solution is 10, the tin plating temperature is 50°C, and the mechanical stirring speed is 100rpm;

[0124] S3. coating the surface of the glass fiber cloth obtained in step S1 with a lead-tin alloy composite layer and coating the chemically tin-plated aluminum or aluminum alloy beam obtained in step S2 with rosin oil, and then subjecting the beam to a heat treatment at a temperature of 100° C. to obtain an aluminum conductive beam;

[0125] 2) Preparation of copper-aluminum composite conductive head: The preparation method of the copper-aluminum composite conductive head has the following specific steps:

[0126] S1. The T1 copper substrate was pickled with 10% sulfuric acid and washed with deionized water, then immersed in an acidic chemical tin plating solution, tinned at a temperature of 40 ° C for 20 min, washed with deionized water and dried to obtain a chemically tinned copper substrate;

[0127] The acidic chemical tin plating solution contains 20 g / L stannous chloride, 10 g / L nitrilotriacetic acid, 40 g / L thiourea, 20 ml / L commercial concentrated hydrochloric acid, 20 g / L sodium citrate and 20 g / L sodium hypophosphite, and the pH value of the acidic chemical tin plating solution is maintained at 0.5;

[0128] S2. The chemically tinned copper substrate is placed in the mold cavity, and the aluminum alloy is extruded into the cavity at a temperature of 600°C, and the copper-aluminum composite conductive head is obtained by cooling, crystallizing and solidifying at a constant pressure; wherein the extrusion pressure is 1MPa and the extrusion rate is 6 m / s;

[0129] 3) The anode composite rod is prepared by adopting a fully automated production line process: the aluminum wire is sequentially subjected to alkaline washing, deionized water washing, ultrasonic cleaning, acid activation treatment, deionized water washing, zinc immersion treatment, deionized water washing, pyrophosphate copper plating treatment, deionized water washing, methanesulfonate lead-tin rare earth alloy plating treatment, deionized water washing, fluoroboric acid system lead-bismuth-antimony-rare earth nano-cobalt powder treatment, deionized water washing, extrusion and drawing composite rod treatment, pickling and oil removal, deionized water washing and drying, spraying of aluminum-titanium-boron composite particles coated with lead and silver on the surface, heat treatment, winding and cutting to a fixed length to obtain the anode composite rod;

[0130] The alkaline washing solution contains 10g / L NaOH and 5g / L Na2CO3, the alkaline washing temperature is 50℃, and the alkaline washing soaking time is 20s;

[0131] In terms of mass percentage, the acid activation solution contains 20% nitric acid and 1% tartaric acid, and the acid activation treatment time is 5s;

[0132] The zinc immersion solution contains 15 g / L zinc oxide, 80 g / L NaOH, 10 g / L potassium sodium tartrate, 0.5 g / L ferric chloride and 0.5 g / L nickel sulfate, and the zinc immersion treatment time is 30 s;

[0133] The pyrophosphate copper plating solution contains 50g / L copper pyrophosphate, 200g / L potassium pyrophosphate, 5g / L ammonium citrate and 1g / L glycerol. The anode of the pyrophosphate copper plating is copper T1, the electroplating temperature is 40°C, and the cathode current density is 1A / dm 2 , time is 3min;

[0134] The methanesulfonate lead-tin rare earth alloy plating solution contains 80g / L lead methanesulfonate, 5g / L stannous methanesulfonate, 60g / L methanesulfonic acid, 2g / L CeO2, 1ml / L emulsifier (emulsifier is OP-10) and 0.05g / L PVP; the anode of the methanesulfonate lead-tin rare earth alloy plating is Pb-1% Sn alloy, the cathode current density is 1A / dm 2 , electroplating temperature is 20℃, time is 10min;

[0135] The fluoroboric acid system lead bismuth antimony-rare earth nano-cobalt powder plating solution contains 150g / L lead acetate, 50g / L fluoroboric acid, 2g / L antimony potassium tartrate, 2g / L CeO2, 1g / L nano-cobalt powder, 0.05g / L gelatin and 0.05g / L polyethylene glycol 6000; the anode of the fluoroboric acid system lead bismuth antimony-rare earth nano-cobalt powder plating is Pb-0.5% Sb alloy, the cathode current density is 6A / dm 2 , the electroplating temperature is 20℃ and the time is 30min;

[0136] The extrusion-drawn composite rod treatment was carried out in an extrusion coating machine, with a die temperature of 100 °C and a pulling speed of 1 m / min;

[0137] The pickling solution contains 50 g / L sodium acetate, 10 g / L glucose and 1 g / L tartaric acid;

[0138] The heat treatment is carried out in a hot air furnace at a temperature of 300°C for 3 min;

[0139] The method for treating aluminum-titanium-boron composite particles coated with lead-silver on the spray surface comprises the following specific steps:

[0140] S1. The aluminum titanium boron particles were degreased with a sodium hydroxide solution, activated with a HNO3 solution for 1 min, roughened with a HCl solution for 1 min, sensitized with a stannous chloride solution for 5 min, and activated with a silver nitrate solution for 3 min to obtain pretreated aluminum titanium boron particles;

[0141] The concentration of sodium hydroxide solution is 5%, the concentration of HNO3 solution is 5%, the concentration of HCl solution is 5%, the concentration of stannous chloride solution is g / LSnCI2+5ml / LHCl, and the concentration of silver nitrate solution is 1g / L;

[0142] S2. placing the pretreated aluminum-titanium-boron particles in a chemical lead-silver plating solution for chemical composite plating, washing with deionized water, and performing solid-liquid separation to obtain aluminum-titanium-boron composite particles coated with lead-silver;

[0143] The chemical lead-silver plating solution contains 10 g / L PbCl2, 10 g / L nitrilotriacetic acid, 10 g / L sodium citrate, 3 ml / L TiCl3 (mass concentration is 20%) and 1 g / L nano silver powder. The pH value of the chemical lead-silver plating solution is adjusted to 7.0 by ammonia water, and the time of chemical composite plating is 30 min.

[0144] S3. The lead-silver-coated aluminum-titanium-boron composite particles are sprayed on the surface of the extruded and drawn composite rod by a cold spray machine;

[0145] 4) welding the copper-aluminum composite conductive head and one end of the aluminum conductive beam, welding the anode composite rod to the bottom of the aluminum conductive beam to form a fence-type aluminum-based composite anode plate bracket, horizontally die-casting multiple layers of conductive reinforcing ribs on the fence-type aluminum-based composite anode plate bracket, installing insulating sheaths on both sides of the fence-type aluminum-based composite anode plate bracket, and installing insulators on the fence-type aluminum-based composite anode plate bracket to obtain an energy-saving and high-strength fence-type composite anode plate for non-ferrous metal electrowinning;

[0146] In this embodiment, the energy-saving high-strength fence-type composite anode plate for nonferrous metal electrowinning is electrolyzed in an acidic zinc electrolyte under the following electrolysis conditions: the zinc ion concentration of the electrolyte is 50 g / L, the sulfuric acid concentration is 160 g / L, and the Mn 2+ 12g / L, current density 700A / m 2 The electrolysis temperature is 40°C. The electrical efficiency of the gradient composite lead dioxide anode is 3.0% higher than that of the traditional lead-calcium (0.06%) and silver (0.3%) alloy anode plate, the cell voltage is reduced by 5%, the life is extended by 1.2 times, and the manganese dioxide particles covering the electrode surface are reduced by 40%.

[0147] Embodiment 3: The energy-saving high-strength fence type composite anode plate for non-ferrous metal electrowinning of this embodiment is basically the same as the energy-saving high-strength fence type composite anode plate for non-ferrous metal electrowinning of embodiment 1, except that: the thickness of the zinc layer in the transition layer 72 is 2 μm, the thickness of the copper layer is 8 μm, and the thickness of the lead-tin-rare earth composite layer is 20 μm; the mass percentage of tin in the lead-tin-rare earth composite layer is 30%, the mass percentage of rare earth is 0.5%, and the balance is lead; the mass percentage of the lead-bismuth-antimony / rare earth-nano cobalt composite layer 73 is 20 μm, and the mass percentage of the lead-bismuth-antimony / rare earth-nano cobalt composite layer 73 is 20 μm. Taking the mass fraction of the lead-silver composite coating 74 coated on the surface of the aluminum-titanium-boron particles as 100%, bismuth accounts for 1.0%, antimony accounts for 5%, rare earth accounts for 0.1%, nano-cobalt accounts for 0.5%, and the balance is Pb; in the lead-silver composite coating 74 coated on the surface of the aluminum-titanium-boron particles, the particle size of the aluminum-titanium-boron particles is 0.5 mm, and the thickness of the lead-silver composite coating is 0.6 mm; taking the mass fraction of the lead-silver composite coating 74 coated on the surface of the aluminum-titanium-boron particles as 100%, lead accounts for 12%, silver accounts for 3% (silver is 50 nm nano-silver powder), titanium accounts for 5%, boron accounts for 1%, and the balance is aluminum;

[0148] The copper-aluminum composite conductive head 2 is prepared by a die-casting method and consists of an inner copper rod 22 and an aluminum coating layer 21; the inner copper rod 22 in the copper-aluminum composite conductive head 2 is a heterogeneous structure with a thickness of 20 mm; the aluminum coating layer 21 includes a tin transition layer and an aluminum surface layer, the tin transition layer is 10 μm thick, and the aluminum surface layer is 20 mm thick;

[0149] The aluminum conductive beam 1 includes 6061 aluminum alloy, glass fiber cloth and lead-tin layer from inside to outside in sequence; a coolant circulation channel parallel to the aluminum conductive beam 1 is opened in the aluminum conductive beam 1, and the coolant circulation channel is filled with anti-oxidation circulating water to cool the aluminum conductive beam; the height of the aluminum conductive beam 1 is 60 mm, the thickness is 40 mm, the thickness of the glass fiber cloth is 2 mm, the thickness of the lead-tin layer is 2 mm, and the diameter of the coolant circulation channel is 10 mm;

[0150] The conductive reinforcing rib 6 is a lead-tin-antimony alloy reinforcing rib, with the mass fraction of the lead-tin-antimony alloy being 100%, lead accounting for 88%, tin accounting for 6%, and antimony accounting for 6%; the conductive reinforcing rib 6 is 100 mm wide and 20 mm thick;

[0151] The preparation method of energy-saving high-strength fence type composite anode plate for non-ferrous metal electrowinning comprises the following specific steps:

[0152] 1) Preparation of aluminum conductive beam: The preparation method of the aluminum conductive beam includes the following specific steps:

[0153] S1. The glass fiber cloth is sensitized and activated at room temperature, and then immersed in an alkaline chemical tin plating solution for tin plating for 30 minutes, and then placed in an alkaline lead-tin electroplating solution for electroplating a lead-tin alloy for 8 hours to obtain a lead-tin alloy composite layer coated on the surface of the glass fiber cloth;

[0154] The sensitizing solution is 20g / LSnCI2+20ml / L HCl solution, and the sensitizing time is 10min;

[0155] The activation solution was 3 g / L AgNO3 solution, and the ultrasonic activation time was 10 min;

[0156] The alkaline chemical tin plating solution contains 150 g / L sodium stannate and 30 g / L potassium hydroxide, the pH value of the alkaline chemical tin plating solution is 12, the tin plating temperature is 70°C, and the mechanical stirring speed is 300 rpm;

[0157] The alkaline lead-tin plating solution contains 30g / L lead oxide, 40g / L sodium stannate, 200g / L potassium sodium tartrate and 40g / L disodium ethylenediaminetetraacetic acid. The pH of the alkaline lead-tin plating solution is 13. The temperature of the lead-tin alloy electroplating is 50°C and the current density is 2A / dm 2 ;

[0158] S2. The aluminum beam is sandblasted with 40 mesh A12O3 and then activated with hydrochloric acid, and then placed in an alkaline chemical tin plating solution for 30 minutes, and then a cooling liquid circulation channel parallel to the aluminum or aluminum alloy beam is opened in the aluminum beam to obtain a chemically tinned aluminum beam; wherein the mass concentration of hydrochloric acid is 15%, and the hydrochloric acid activation treatment time is 10 minutes; the alkaline chemical tin plating solution contains 150g / L sodium stannate and 30g / L potassium hydroxide, the pH value of the alkaline chemical tin plating solution is 12, the tin plating temperature is 70°C, and the mechanical stirring speed is 300rpm;

[0159] S3. The surface of the glass fiber cloth obtained in step S1 is coated with a lead-tin alloy composite layer and the chemically tinned aluminum or aluminum alloy beam obtained in step S2 is coated with rosin oil, and then subjected to a heat treatment at a temperature of 200° C. to obtain an aluminum conductive beam;

[0160] 2) Preparation of copper-aluminum composite conductive head: The preparation method of the copper-aluminum composite conductive head has the following specific steps:

[0161] S1. The T1 copper substrate was pickled with 20% sulfuric acid and washed with deionized water, then immersed in an acidic chemical tin plating solution, tinned at a temperature of 80 ° C for 60 min, washed with deionized water and dried to obtain a chemically tinned copper substrate;

[0162] The acidic chemical tin plating solution contains 40 g / L stannous chloride, 40 g / L nitrilotriacetic acid, 80 g / L thiourea, 40 ml / L commercial concentrated hydrochloric acid, 60 g / L sodium citrate and 60 g / L sodium hypophosphite, and the pH value of the acidic chemical tin plating solution is maintained at 2.0;

[0163] S2. The chemically tinned copper substrate is placed in the mold cavity, and the aluminum alloy is extruded into the cavity at a temperature of 700°C, and the copper-aluminum composite conductive head is obtained by cooling, crystallizing and solidifying at a constant pressure; wherein the extrusion pressure is 6MPa and the extrusion rate is 12 m / s;

[0164] 3) The aluminum wire is sequentially subjected to alkaline washing, deionized water washing, ultrasonic cleaning, acid activation treatment, deionized water washing, zinc immersion treatment, deionized water washing, pyrophosphate copper plating treatment, deionized water washing, methanesulfonate lead-tin rare earth alloy plating treatment, deionized water washing, fluoroboric acid system lead-bismuth-antimony-rare earth nano-cobalt powder treatment, deionized water washing, extrusion and drawing composite rod treatment, pickling and oil removal, deionized water washing and drying, spraying of aluminum-titanium-boron composite particles coated with lead and silver on the surface, heat treatment, winding and cutting to a fixed length to obtain an anode composite rod;

[0165] The alkaline washing solution contains 100 g / L NaOH and 20 g / L Na2CO3, the alkaline washing temperature is 70°C, and the alkaline washing soaking time is 100 s;

[0166] In terms of mass percentage, the acid activation solution contains 50% nitric acid and 5% tartaric acid, and the acid activation treatment time is 30s;

[0167] The zinc immersion solution contains 30 g / L zinc oxide, 120 g / L NaOH, 30 g / L potassium sodium tartrate, 2 g / L ferric chloride and 1.5 g / L nickel sulfate, and the zinc immersion treatment time is 60 s;

[0168] The pyrophosphate copper plating solution contains 100g / L copper pyrophosphate, 400g / L potassium pyrophosphate, 20g / L ammonium citrate and 5g / L propylene glycol. The anode of the pyrophosphate copper plating is copper T1, the electroplating temperature is 70°C, and the cathode current density is 6A / dm 2 , time is 30min;

[0169] The methanesulfonate lead-tin rare earth alloy plating solution contains 120g / L lead methanesulfonate, 20g / L stannous methanesulfonate, 120g / L methanesulfonic acid, 10g / L CeO2, 10ml / L emulsifier (emulsifier is OP-10) and 1.0g / L PVP; the anode of the methanesulfonate lead-tin rare earth alloy plating is Pb-5% Sn alloy, the cathode current density is 5A / dm 2 , electroplating temperature is 50℃, time is 90min;

[0170] The fluoroboric acid system lead bismuth antimony-rare earth nano cobalt powder plating solution contains 300g / L lead acetate, 200g / L fluoroboric acid, 12g / L antimony potassium tartrate, 10g / L CeO2, 6g / L nano cobalt powder, 2g / L gelatin, and 1.0g / L polyethylene glycol 6000; the anode of the fluoroboric acid system lead bismuth antimony-rare earth nano cobalt powder plating is Pb-3% Sb alloy, and the cathode current density is 6A / dm2 , the electroplating temperature is 60℃ and the time is 90min;

[0171] The extrusion-drawn composite rod treatment was carried out in an extrusion coating machine, with a die temperature of 300 °C and a pulling speed of 10 m / min;

[0172] The pickling solution contains 300g / L sodium acetate, 200g / L glucose, and 20g / L tartaric acid;

[0173] The heat treatment is carried out in a hot air furnace at a temperature of 500°C for 5 min;

[0174] The method for treating aluminum-titanium-boron composite particles coated with lead-silver on the spray surface comprises the following specific steps:

[0175] S1. The aluminum titanium boron particles were degreased with a sodium hydroxide solution, activated with a HNO3 solution for 3 min, roughened with a HCl solution for 4 min, sensitized with a stannous chloride solution for 20 min, and activated with a PdCl2 solution for 5 min to obtain pretreated aluminum titanium boron particles;

[0176] The concentration of sodium hydroxide solution is 10%, the concentration of HNO3 solution is 10%, the concentration of HCl solution is 10%, the concentration of stannous chloride solution is 30g / LSnCI2+30ml / L HCl, and the concentration of PdCl2 solution is 1g / L;

[0177] S2. placing the pretreated aluminum-titanium-boron particles in a chemical lead-silver plating solution for chemical composite plating, washing with deionized water, and performing solid-liquid separation to obtain aluminum-titanium-boron composite particles coated with lead-silver;

[0178] The chemical lead-silver plating solution contains 20 g / L PbCl2, 40 g / L nitrilotriacetic acid, 50 g / L sodium citrate, 10 ml / L TiCl3 (mass concentration is 20%) and 5 g / L nano silver powder. The pH value of the chemical lead-silver plating solution is adjusted to 8.0 by ammonia water, and the time of chemical composite plating is 120 min.

[0179] S3. The lead-silver-coated aluminum-titanium-boron composite particles are sprayed on the surface of the extruded and drawn composite rod by a cold spray machine;

[0180] 4) welding the copper-aluminum composite conductive head and one end of the aluminum conductive beam, welding the anode composite rod to the bottom of the aluminum conductive beam to form a fence-type aluminum-based composite anode plate bracket, horizontally die-casting multiple layers of conductive reinforcing ribs on the fence-type aluminum-based composite anode plate bracket, installing insulating sheaths on both sides of the fence-type aluminum-based composite anode plate bracket, and installing insulators on the fence-type aluminum-based composite anode plate bracket to obtain an energy-saving and high-strength fence-type composite anode plate for non-ferrous metal electrowinning;

[0181] In this embodiment, the energy-saving high-strength fence-type composite anode plate for nonferrous metal electrowinning is electrolyzed in an acidic zinc electrolyte under the following electrolysis conditions: the zinc ion concentration of the electrolyte is 50 g / L, the sulfuric acid concentration is 160 g / L, and the Mn 2+ 12g / L, current density 1000A / m 2 The electrolysis temperature is 40°C. The electrical efficiency of the fence-type composite anode is 3.0% higher than that of the traditional lead-calcium (0.06%) and silver (0.3%) alloy anode plate, the cell voltage is reduced by 10%, the life is extended by 1.5 times, and the manganese dioxide particles covering the electrode surface are reduced by 60%.

[0182] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. An energy-saving and high-strength fence-type composite anode plate for non-ferrous metal electrowinning, characterized in that: It comprises an aluminum conductive beam (1), a copper-aluminum composite conductive head (2) being fixedly provided at the end of the aluminum conductive beam (1), a fence-type aluminum-based composite anode plate support (3) being fixedly provided at the bottom of the aluminum conductive beam (1), multiple layers of horizontal conductive reinforcing ribs (6) being fixedly provided along the longitudinal direction of the fence-type aluminum-based composite anode plate support (3), both sides of the fence-type aluminum-based composite anode plate support (3) being covered with insulating sheaths (4), and both ends of the conductive reinforcing ribs (6) being provided in the insulating sheaths (4); The fence-type aluminum-based composite anode plate support (3) is composed of a plurality of parallel anode composite rods (7), wherein the anode composite rods (7) include, from the inside to the outside, an aluminum alloy rod (71), a transition layer (72), a lead-bismuth-antimony / rare earth-nano cobalt composite layer (73), and a lead-silver composite coating (74) coated on the surface of aluminum-titanium-boron particles; wherein the transition layer (72) includes, from the inside to the outside, a zinc layer, a copper layer, and a lead-tin-rare earth composite layer; The aluminum conductive beam (1) comprises aluminum or aluminum alloy, glass fiber cloth and lead-tin layer from inside to outside in sequence; A cooling liquid circulation channel parallel to the aluminum conductive beam (1) is provided in the aluminum conductive beam (1), and the cooling liquid circulation channel is filled with cooling liquid.

2. The energy-saving and high-strength fence-type composite anode plate for non-ferrous metal electrowinning according to claim 1, characterized in that: The copper-aluminum composite conductive head (2) consists of an inner copper rod (22) and an aluminum cladding layer (21).

3. The energy-saving and high-strength fence-type composite anode plate for non-ferrous metal electrowinning according to claim 1, characterized in that: The height of the aluminum conductive beam (1) is 10-60 mm, the thickness is 10-40 mm, the thickness of the glass fiber cloth is 0.2-2 mm, the thickness of the lead-tin layer is 0.1-2 mm, and the diameter of the coolant circulation channel is 0.5-10 mm.

4. The energy-saving and high-strength fence-type composite anode plate for nonferrous metal electrowinning according to claim 2, characterized in that: The inner copper rod (22) in the copper-aluminum composite conductive head (2) is a heterogeneous structure with a thickness of 5 to 20 mm; the aluminum coating layer (21) includes a tin transition layer and an aluminum surface layer, the tin transition layer has a thickness of 1 to 10 μm, and the aluminum surface layer has a thickness of 5 to 30 mm.

5. The energy-saving and high-strength fence-type composite anode plate for nonferrous metal electrowinning according to claim 1, characterized in that: The thickness of the zinc layer in the transition layer (72) is 0.5-2 μm, the thickness of the copper layer is 3-8 μm, and the thickness of the lead-tin-rare earth composite layer is 4-20 μm; the mass percentage of tin in the lead-tin-rare earth composite layer is 5-30%, the mass percentage of rare earth is 0.01-0.5%, and the balance is lead.

6. The energy-saving and high-strength fence-type composite anode plate for nonferrous metal electrowinning according to claim 1, characterized in that: Taking the mass fraction of the lead-bismuth-antimony / rare earth-nano-cobalt composite layer (73) as 100%, bismuth accounts for 0.01-1%, antimony accounts for 0.5-5%, rare earth accounts for 0.01-0.1%, nano-cobalt accounts for 0.01-0.5%, and the balance is Pb.

7. The energy-saving and high-strength fence-type composite anode plate for nonferrous metal electrowinning according to claim 1, characterized in that: In the lead-silver composite coating (74) coated on the surface of aluminum-titanium-boron particles, the particle size of the aluminum-titanium-boron particles is 0.05-0.5 mm, and the thickness of the lead-silver composite coating is 0.1-0.6 mm; based on the mass fraction of the lead-silver composite coating (74) coated on the surface of the aluminum-titanium-boron particles as 100%, lead accounts for 5-12%, silver accounts for 0.5-3.0%, titanium in the aluminum-titanium-boron particles accounts for 1-5%, boron accounts for 0.1-1%, and the remainder is aluminum.

8. The method for preparing the energy-saving and high-strength fence-type composite anode plate for nonferrous metal electrowinning according to any one of claims 1 to 7, characterized in that: The specific steps are as follows: 1) The aluminum wire is sequentially subjected to alkaline washing, deionized water washing, ultrasonic cleaning, acid activation treatment, deionized water washing, zinc immersion treatment, deionized water washing, pyrophosphate copper plating treatment, deionized water washing, methanesulfonate lead-tin rare earth alloy plating treatment, deionized water washing, fluoroboric acid system lead-bismuth-antimony-rare earth nano-cobalt powder treatment, deionized water washing, extrusion and drawing composite rod treatment, pickling and oil removal, deionized water washing and drying, spraying of aluminum-titanium-boron composite particles coated with lead and silver on the surface, heat treatment, winding and cutting to a fixed length to obtain an anode composite rod; 2) The copper-aluminum composite conductive head is welded to one end of the aluminum conductive beam, and the anode composite rod is welded to the bottom end of the aluminum conductive beam to form a fence-type aluminum-based composite anode plate bracket. Multi-layer conductive reinforcement ribs are horizontally die-cast on the fence-type aluminum-based composite anode plate bracket. Insulating sheaths are installed on both sides of the fence-type aluminum-based composite anode plate bracket. Insulators are installed on the fence-type aluminum-based composite anode plate bracket to obtain energy-saving and high-strength fence-type composite anode plates for non-ferrous metal electrowinning.

Citation Information

Patent Citations

  • Non ferrous metal is fence type anode plate for electrodeposition

    CN204779871U